2-[(2,4-Dihydroxybenzylidene)amino]-3′,6′-bis(ethylamino)spiro[isoindoline-1,9′-xanthen]-3-one - Xu, Zhi-Hong (International Union of Crystallography, 2010)
The title compound, C(35)H(36)N(4)O(4), was prepared as a spirolactam ring formation of rhodamine B dye for comparison with a ring-opened form. The xanthene ring system is approximately planar. The r.m.s. deviation from planarity is 0.064 (6) Å for the xanthene ring. The dihedral angles formed by the spirolactam and 2,4-dihydroxybenzene rings with the xanthene ring system are 86.6 (9) and 88.0 (9)°, respectively.